Strategi Pemulihan Sektor Pariwisata Pada Era Adaptasi Kebiasaan Baru (New Normal) di Kalimantan Selatan - Riswan Hidayat; Noor Rahmini (Ecoplan, 2022)
This study aims to determine the state of Kalsel tourism during covid-19 and the strategic plan of the Kalsel Tourism Office in recovering the tourism industry, identify the driving and inhibiting factors in the tourism recovery process, and determine the right strategy for recovery. Researchers used descriptive methods and swot analysis using eight respondents. The results of the study show that covid-19 has an impact on the tourism sector, but in the first quarter of 2020, there was a teacher haul event attended by millions of people, and the realization of visits reached 100%. The tourism Office carries out several strategies by promoting tourism, conducting events with health protocols, and providing support to destinations, industries, and tourism actors. In addition, the CHSE program is also implemented. The strategy obtained from identifying the driving and inhibiting factors is to maximize your funds for health protocols and conduct events with standardized health protocols.